Respon Pertumbuhan Tanaman Jagung (Zea Mays L) dengan Pemberian Kapur pada Berbagai Media Tanam - Afri Rona Diyanti; Yopa Dwi Mutia; M. Fauzan Farid Al Hamdi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the response of corn plants to the growth of corn plants by giving lime to various growing media. The experiment was carried out in Kampung Jambak Kel. Batipuh Panjang from March to May 2021. This study used factorial RAL, the first factor was marginal soil consisting of 4 levels, namely peat soil, ultisol soil, sandy soil and saline soil and the second factor was giving lime consisting of 2 levels, namely without lime and lime with 4 replicates. Based on the results of the study, lime application on peat soil showed optimal vegetative growth. Giving lime to the growing media showed a significant effect on the growth of soil pH, plant height, number of leaves and leaf color of corn plants.